Centro de atención integral para niños habitantes de calle en la ciudad de Bogotá (2018)
The project focuses, from the academic exercise, on analyzing and reflecting on quality life of street children in the city of Bogotá, through the recovery of fundamental principles understood as: “rights, affection, solidarity and respect reciprocal among all its members”, and its relationship with the primary family network, defined “as the most basic unit of society, and in it, the development of values, objectives of life and identities, which allow the adaptation of the individual to society. (ICBF-IOM, 2008, pp. 21), in favor of the cognitive development of street children through activities that strengthen the bases for social heterogeneity, carried out in the “Attention Center for Street Children” in order to improve their living conditions.